Influenza antivirals: update - Hayden, Frederick G. (Henry Stewart Talks, 2011)
Antivirals for influenza-historical perspectives, Influenza virus replication and sites of inhibition, Principal antiviral agents for influenza, Detecting the emergence of resistant virus, Influenza prevention in households, Antiviral-resistant viruses with differing circulation, NA inhibitors for treatment, NA inhibitors for chemoprophylaxis, Post-exposure prophylaxis (PEP), NAI resistance, Newer and investigational influenza antivirals, Antiviral combinations